Correlation Between Tumor Cell Differentiation and CEA Levels in Patients with Adenocarcinoma of the Rectum - Rudiman, Reno; Lukman, Kiki; Barr, Tubagus Izzul (Faculty of Medicine, Universitas Padjadjaran, 2020)
Adenocarcinoma of the rectum is the most common colorectal cancer in Indonesia. This cancer has the highest recurrence after curative surgical therapy with or without adjuvant therapy. With the advancing modern histopathology and molecular biology, the prognosis after therapy can be predicted through surveillance using tumor cell differentiation and carcinoembryonic antigen (CEA). The aim of this study was to analyze the correlation between tumor cell differentiation and serum CEA level in patients with adenocarcinoma of the rectum in Dr. Hasan Sadikin General Hospital Bandung, Indonesia. This was a retrospective observational analytic study conducted from January 2018- January 2019. There were 36 patients involved in this study consisting of 3 patients (8.3%) diagnosed with Stage II, 10 patients (27.7%) with Stage IIIA, 20 patients (55.5%) with stage IIIB, and 3 patients (8.3%) with stage IIIC. On histopathological examination, it was demonstrated that19 patients (52.8%) were well-differentiated, 15 patients (41.7%) were moderately differentiated, and 2 patients (5.6%) were poorly differentiated. The mean CEA level (CI 95%) for well-differentiated patients before surgery was 138.18 (15.99-260.38) ng/ml while the same level for the moderately differentiated patients was 64.34 (34.34-163.02) ng/ml. The mean CEA level for poorly differentiated patients was 1.55 (6.71-9.81) ng / ml. The result of the Kruskal Wallis test showed a p-value of 0.004. There is a strong correlation between the level of tumor cell differentiation and CEA level. Hubungan Tingkat Diferensiasi Sel Tumor dengan Kadar Ekspresi CEA Pada Pasien Adenokarsinoma Rektum Di Indonesia adenokarsinoma rektum memiliki rekurensi yang tinggi setelah terapi bedah kuratif dengan atau tanpa terapi adjuvan. Prognosisnya setelah terapi dapat diketahui melalui surveilens dengan menggunakan Tingkat diferensiasi sel tumor dan carcinoembryonic antigen (CEA). Penelitian ini bertujuan menilai hubungan diferensiasi sel tumor dengan tingkat ekspresi CEA pada pasien adenokarsinoma rektum di RSUP Dr. Hasan Sadikin Bandung. Penelitian ini merupakan penelitian analitik observasional secara retrospektif. Pengambilan data dilakukan dari rekam medik Poliklinik Bedah Digestif dengan diagnosa adenokarsinoma rektum. Dari 36 pasien, 3 pasien (8,3%) stadium II, 10 pasien (27.7%) Stadium IIIA, 20 pasien (55,5%) stadium IIIB dan 3 pasien (8,3%) sisanya stadium IIIC. Sebanyak 19 pasien (52.8%) memiliki hasil histopatologi well differentiated, 15 pasien (41.7%) moderately differentiated dan 2 pasien (5.6%) poorly differentiated. Mean (CI 95%) kadar CEA sebelum operasi untuk well differentiated adalah 138.18(15.99-260.38) ng/mL, moderately differentiated 64.34(34.34-163.02)ng/ml, poorly differentiated 1.55(6.71-9.81)ng/mL. Uji Kruskal Wallis didapatkan nilai p=0,004 sehingga dapat disimpulkan bahwa terdapat hubungan antara tingkat diferensiasi sel tumor dengan kadar CEA serum sebelum terapi pada pasien adenokarsinoma rektum di RSUP Hasan Sadikin Bandung. Pasien adenokarsinoma rektum preoperatif di RSUP Hasan Sadikin Bandung menunjukkan bahwa semakin baik tingkat diferensiasi sel tumornya semakin tinggi kadar CEAnya di dalam serum.